An exploratory study of SME management in the Middle East. (15th November 2004) - Welsh, Dianne H.B.; Raven, Peter
The Middle East is a growing, lucrative marketplace that recently has captured the interest of the world for political as well as economic reasons with the War in Iraq in 2003. This exploratory study examines the relationship between retail small/medium enterprises (SMEs) management and employee perceptions of customer service on a number of dimensions. The results suggest that managers and employees in the Middle East behave in similar ways to those in western countries, but there are differences, probably related to cultural characteristics. The Middle East is a richly diverse region, a myriad of unique cultures. As the market becomes more sophisticated, the importance of service quality increases. Global retailers can benefit from this study by better understanding the managers and employees in the region that are vital to their success. Implications for practice are discussed.